2020
DOI: 10.1021/acs.iecr.0c03763
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Welding of the UIO-66-NH2 MOF to Cotton Textiles

Abstract: Ionic liquid based fiber welding has been used to attach the metal−organic framework (MOF) UiO-66-NH 2 to cotton fibers. The results show that by controlling the extent of the welding process, it is possible to produce fibers that contain a high surface area (approximately 50−100 m 2 / g), an X-ray diffraction pattern consistent with UiO-66-NH 2 , and fibers that are chemically reactive to dimethyl 4-nitrophenyl phosphate (DMNP), a common chemical weapon simulant. The ionic liquid/MOF welding solution can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In addition, Bunge et al 196 demonstrated two more approaches, namely, direct contact welding and air-brush welding to produce multiple batches of UiO-66-NH 2 embedded cotton textiles using ionic liquid (IL)/MOF as a welding solution. The MOF welded cotton textiles were examined against chemical simulant DMNP and the conversion reaction of DMNP to p-nitrophenoxide was recorded using the UV−vis spectrophotometer over a period of time.…”
Section: Integration Of Mof Into Textile Asmentioning
confidence: 99%
“…In addition, Bunge et al 196 demonstrated two more approaches, namely, direct contact welding and air-brush welding to produce multiple batches of UiO-66-NH 2 embedded cotton textiles using ionic liquid (IL)/MOF as a welding solution. The MOF welded cotton textiles were examined against chemical simulant DMNP and the conversion reaction of DMNP to p-nitrophenoxide was recorded using the UV−vis spectrophotometer over a period of time.…”
Section: Integration Of Mof Into Textile Asmentioning
confidence: 99%
“…Cotton fabric can be especially challenging to coat due to water uptake, fiber variability, and fiber hand changes during processing. However, there are reports of UiO-66 cotton composites predominantly using UiO-66 formed with traditional solvents. In a different study, cotton fabrics were coated with UiO-66-NH 2 with precursors dissolved in dilute acetic acid combined with HCl and NaOH . To the best of our knowledge, no previous study has explored GVL as a green solvent for MOF-fabric composite synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The same approach was also adjusted to inorganic zeolite crystals which can be directly deposited on cellulose fiber via classical methods such as hydrothermal treatment or spray-coating [222,223]. An original approach has been validated recently, using an ionic liquid welding technique to improve the anchoring of UiO-66-NH 2 on cotton [224]. Deposition of pre-formed MOFs by simple immersion of the textile in a suspension have also been reported for the deposit of MOF-808 on cotton [32].…”
Section: Functionalization and Surface Decoration Of The Fibersmentioning
confidence: 99%
“…High degradation efficiencies towards DMNP (i.e. half-lives under 10 min) with UiO-66-NH 2 composites were obtained either using the photothermal effect [244,251,306], some specific synthesis deposition [224,246,247] or by adding an intermediate ALD layer between the fiber and the MOF [253,257,258,304]. The photothermal method converts photon into heat thanks to photothermal agents such as polydopamine (PDA) or graphene.…”
Section: Detoxification In the Presence Of Nemmentioning
confidence: 99%